Insulin-like growth factor 1 (IGF1) affects proliferation and differentiation and wound healing processes in an inflammatory environment with p38 controlling early osteoblast differentiation in periodontal ligament cells. (January 2017) - Reckenbeil, Jan; Kraus, Dominik; Stark, Helmut; Rath-Deschner, Birgit; Jäger, Andreas; Wenghoefer, Matthias; Winter, Jochen; Götz, Werner
Highlights: IGF1 potential for counteracting destructive effects was investigated. IGF1 could antagonize negative effects caused by inflammatory stimuli. P38 is key molecule to bring IGF1 and IL-1β signaling together. IGF1 was able to increase bone cell differentiation and biomineralization. IGF1 showed potential to improve wound healing and proliferation processes. Abstract: Objective: The objective of this study was to investigate effects of insulin-like growth factor 1 (IGF1) on proliferation, wound healing and differentiation processes of human periodontal ligament (PDL) cells under inflammatory conditions and whether the protective, anabolic effects of IGF1 can attenuate unfavorable effects of interleukin-1β (IL-1β). Design: Inflammation was mimicked through cell stimulation with IL-1β. PDL cells were characterized in respect to the presence of components of the IGF system and the responsive potential on IL-1β incubation. Gene expression levels were analyzed by quantitative real-time PCR. Cellular localization of target proteins was visualized using fluorescent-based immunohistochemistry. Effects on cell division were investigated by proliferation assays. Wound healing was analyzed using light microscopic techniques. Differentiation was quantified by measuring biomineralization and osteoblast-specific alkaline phosphatase enzyme activity. Results: PDL cell proliferation and wound healing were positively affected by IGF1 and the combination of IGF1 with IL-1β, while only IL-1β showed negative effects. Biomineralization was enhanced by IGF1, IL-1β, and the combination of both stimulants. Osteoblast differentiation was increased by IL-1β and the combination of IL-1β with IGF1, whereas only IGF1 negatively affected ALP activity. Phosphorylation of p38 was regulated by IL-1β and IGF1. Conclusions: The data presented in this work showed a potential of IGF1 to improve wound healing and proliferation processes and to sustain cell differentiation under inflammatory stimuli in PDL cells.